2017
DOI: 10.3389/fpubh.2017.00203
|View full text |Cite
|
Sign up to set email alerts
|

Using Intervention Mapping for Program Design and Production of iCHAMPSS: An Online Decision Support System to Increase Adoption, Implementation, and Maintenance of Evidence-Based Sexual Health Programs

Abstract: In Texas and across the United States, unintended pregnancy, HIV, and sexually transmitted infections (STIs) among adolescents remain serious public health issues. Sexual risk-taking behaviors, including early sexual initiation, contribute to these public health problems. Over 35 sexual health evidence-based programs (EBPs) have been shown to reduce sexual risk behaviors and/or prevent teen pregnancies or STIs. Because more than half of these EBPs are designed for schools, they could reach and impact a conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…IM has been recognized as a useful method for planning multifaceted implementation strategies [9, 37, 40]. A key feature of IM since its inception [41] has been its utility for developing multifaceted implementation interventions to enhance the adoption, implementation, and maintenance of clinical guidelines [42] and EBIs [4349].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IM has been recognized as a useful method for planning multifaceted implementation strategies [9, 37, 40]. A key feature of IM since its inception [41] has been its utility for developing multifaceted implementation interventions to enhance the adoption, implementation, and maintenance of clinical guidelines [42] and EBIs [4349].…”
Section: Discussionmentioning
confidence: 99%
“…Implementation science is a relatively young field and frameworks to help identify implementation determinants such as CFIR have only recently been developed and operationalized. Nonetheless, exemplary studies can be found [49]. For example, Garbutt and colleagues utilized CFIR to characterize contextual determinants of EBI use, analyzed those determinants systematically via a theoretical framework, identified specific behavior change targets, and then selected relevant implementation strategies [51].…”
Section: Discussionmentioning
confidence: 99%
“…Intervention Mapping is a protocol that guides the design of multi-level health promotion interventions and implementation strategies (13). Since its inception, a key feature of Intervention Mapping (Step 5) has been its utility for developing strategies to enhance the adoption, implementation, and maintenance of clinical guidelines (13) and evidence-based interventions (2026).…”
Section: Intervention Mappingmentioning
confidence: 99%
“…Third, and most relevant for this paper, Intervention Mapping can help planners to develop, select, or tailor implementation strategies to increase adoption, implementation, and sustainability. Since its inception, a key feature of IM, has been its utility for developing implementation strategies to enhance the adoption, implementation, and sustainability (2026), nevertheless, its utility has only recently been recognized by implementation scientists (12, 15, 17, 27). Thus, using Intervention Mapping for initial program development, for program adaptation, and/or for planning implementation can reduce the gap between the development of effective clinical practices and programs and their actual use in healthcare settings and communities (28).…”
Section: Intervention Mappingmentioning
confidence: 99%
“…Determinants of TT use will be compared between high and low users to isolate determinants most likely salient to TT use and those that most likely limit use. Identified determinants will then be mapped to implementation strategies and delivery modalities suggested in the Behavioral Change Wheel as appropriate approaches using an intervention mapping approach [67,68].…”
Section: Discussionmentioning
confidence: 99%